10.1k views
0 votes
2(4x+3)=10x-2

So like how in hell do you do this I’m soooo confused

User Chromos
by
5.1k points

2 Answers

4 votes

Answer:

x = 4

Explanation:

First you want to distribute the terms:

2(4x+3) = 10x-2

8x+6 = 10x-2

then combine like terms:

8x+6 = 10x-2

-8x -8x

6 = 2x-2

+2 +2

8 = 2x

x = 4

User Misterte
by
5.4k points
5 votes

Answer:

4

Solution,

2(4x+3)=10x-2

or,8x+6=10x-2

or,8x-10x=-2-6

or,-2x=-8

or,X=-8/-2

X=4

Hope it helps

Good luck on your assignment

User Hacking Life
by
5.2k points